Lotus Seed Tempeh Innovation to Increasing Local Food Availability Through Sustainable Alternatives - Khosyiati, Nur Evirda; Setiawan, Rizal Justian; Ma'ruf, Khakam; Azizah, Nur (jurnal makanan tropis dan teknologi agroindustri, 2024)
Limited food availability poses a significant challenge in keeping pace with rapid population growth. The impact is seen in the 30.8% of children under five in Indonesia who are stunted, signaling a serious nutritional problem. To solve this problem, it is important to find solutions that are healthy and affordable for the community. One of Indonesia's popular, affordable and versatile specialties is tempeh. However, the high consumption of tempeh poses a problem of domestic soybean availability for producers, prompting the search for alternative ingredients in the manufacture of tempeh. Lotus Fruit Seeds (Nymphaea sp.) were identified as a potential substitute for soybeans in making tempeh. The 71.06% carbohydrate and 10.86% protein content in these seeds offers an attractive alternative. This study attempted to use lotus fruit seeds as a raw material for tempeh, while gauging public responses to this product in terms of color, price, taste and aroma. Based on the results of the proximate analysis, the best experiment for processing tempeh from lotus seeds is boiling twice for 15 minutes each, because it can produce a high amount of protein, 37.38%. This study tried to use lotus fruit seeds as raw material for tempeh, while measuring public response to this product in terms of color, price, taste, and aroma. The results showed that tempeh from lotus fruit seeds has similar characteristics to soybean tempeh, the process of making tempeh from lotus seeds is relatively similar to soybean tempeh, although further research is needed to optimize the use of lotus. This has the potential to increase the economic value of lotus into a more meaningful alternative in food fulfillment in Indonesia.